Window on the World of Violence Against Children Outside of Family Care in Uganda: Pushing the Limits of Child Participation in Research and Policy-Making through Youth-Driven Participatory Action Research (YPAR) - Ritterbusch, Amy E.; Boothby, Neil; Mugumya, Firminus; Meyer, Sarah; Wanican, Joyce; Bangirana, Clare; Nyende, Noah; Ampumuza, Doreen; Apota, John (My University, 2007)
From within the supportive environment of the AfriChild Center housed at Makerere University in Kampala, Uganda, our interdisciplinary, intergenerational and multicountry research team launched the qualitative violence against children (VAC) project as a means of opening a window on children’s worlds of violence and resilience, inside and outside of households, in order to catalyze child-focused policy making and community-driven transformations in society. Within households, our research team focused on parents and other adults in the community as catalysts of change through positive parenting practices (see Boothby et al., 2017). In contexts outside of households and family care, our research team focused on children as the catalysts of change through their participation in the research and dissemination process. In this paper, we place children living outside of family care at the center of the stories we will tell and at the center of our methodological reflections surrounding child-focused research and policymaking.
Keywords: Children; Family Care; World of Violence